Bizionia argentinensis sp. nov., isolated from surface marine water in Antarctica - Bercovich, A.; Vázquez, Susana Claudia; Yankilevich, Patricio; Coria, Silvia Herminda; Foti, M.; Hernandez, E.; Vidal, A.; Ruberto, Lucas Adolfo Mauro; Melo, C.; Marenssi, S.; Criscuolo, M.; Memoli, M.; et al. (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY)
A marine bacterial strain, designated strain JUB59T, was isolated from surface seawater in Antarctica and subsequently characterized. Cells were found to be Gram-negative, non-motile rods forming butyrous, shiny, yellowish orange colonies on marine agar. Growth occurred at 2– 28 6C (optimally at 22–25 6C) but not at 30 6C; Na+ ions were required, but 9% NaCl (w/v) was not tolerated. Phylogenetic analysis, based on comparisons of the complete 16S rRNA gene sequence of the novel isolate with the sequences of closely related strains, showed that strain JUB59T belonged to the family Flavobacteriaceae, representing a novel species of the genus was not tolerated. Phylogenetic analysis, based on comparisons of the complete 16S rRNA gene sequence of the novel isolate with the sequences of closely related strains, showed that strain JUB59T belonged to the family Flavobacteriaceae, representing a novel species of the genus Antarctica and subsequently characterized. Cells were found to be Gram-negative, non-motile rods forming butyrous, shiny, yellowish orange colonies on marine agar. Growth occurred at 2– 28 6C (optimally at 22–25 6C) but not at 30 6C; Na+ ions were required, but 9% NaCl (w/v) was not tolerated. Phylogenetic analysis, based on comparisons of the complete 16S rRNA gene sequence of the novel isolate with the sequences of closely related strains, showed that strain JUB59T belonged to the family Flavobacteriaceae, representing a novel species of the genus was not tolerated. Phylogenetic analysis, based on comparisons of the complete 16S rRNA gene sequence of the novel isolate with the sequences of closely related strains, showed that strain JUB59T belonged to the family Flavobacteriaceae, representing a novel species of the genus T, was isolated from surface seawater in Antarctica and subsequently characterized. Cells were found to be Gram-negative, non-motile rods forming butyrous, shiny, yellowish orange colonies on marine agar. Growth occurred at 2– 28 6C (optimally at 22–25 6C) but not at 30 6C; Na+ ions ...